Jalan Terjal UMKM dan Pedagang Kecil Bertahan di Tengah Pandemi Covid-19 dan Ancaman Krisis Ekonomi Global - Beni Dwi Komara; Heri Cahyo Bagus Setiawan; Aries Kurniawan (Universitas Pendidikan Nasional, 2020)
ABSTRACTWednesday, April 1, 2020, Minister of Finance Sri Mulyani Indrawati said that the four sectors most affected by the corona Covid-19 epidemic were households, MSMEs, corporations, and the financial sector. Households will experience a significant decline in terms of consumption because the community is no longer active outside the home so that purchasing power is decreasing and threatened with loss of income because they cannot work to fulfill their basic needs especially for poor and vulnerable families in the informal sector. The micro small and medium business sector (MSME) is under pressure due to not being able to conduct business activities so that the ability to meet credit obligations is disrupted, this increases the bank's Non-Performing Loans (NPL) for MSMEs further worsening economic conditions. At the time of the 1997-1998 crisis where SMEs as economic saviors, now suffered a huge blow because there are restrictions on economic and social activities. (Tempo, 2020). This research is to find out the economic impact in the co-19 pandemic vortex that is happening in the community, especially for MSMEs & small traders and to know how they can take to survive the global crisis that is in front of their eyes? Will they return to being heroes like during the 1997-1998 crisis or will it fall this time.